Optimalisasi Strategi Idarah: Studi Kasus Pengelolaan Masjid Agung Kauman di Kota Semarang - Fadilah, Miftahul; Asy'arie, Bima Fandi; Latif, Abdul (UIN Raden Mas Said Surakarta, 2024)
A mosque is a building built with certain limits to worship Allah Almighty. In this modern era, the existence of a mosque also requires blood so that it can be managed optimally; the meaning of the blood has meanings called “management,” “arrangement,” and “management.” This research method is field research with a qualitative approach. As for how to collect data through observation, in-depth interviews, and documentation. This study aims to find out how (1) the blood strategy of the Great Mosque of Kauman Semarang and (2) Supporting and inhibiting factors in the blood of the Great Mosque of Kauman in Semarang City. The data obtained are: First, the blood of the Great Mosque of Kauman Semarang can be said to be good, because from the data collected with the daily mosque secretary there are security guards and marbots who handle mosque security and administration runs in an orderly manner. Second, the supporting factor of the Great Kauman Semarang mosque is its very strategic location, the management always considers that the mosque building is always in good condition, funding is obtained from other sources, and the mosque function is used for positive activities. However, the inhibiting factors that researchers found were a lack of coordination in physical management in the long run, youth reluctant to contribute, and delays in working on financial statements.